Near-Infrared (NIR) Study of Hydrogen Bonding of Methanol Molecules in Polar and Nonpolar Solvents: An Approach from Concentration-Dependent Molar Absorptivity. Issue 10 (October 2014) - Mikami, Yuho; Ikehata, Akifumi; Hashimoto, Chihiro; Ozaki, Yukihiro
Differences in the hydrogen-bonding states of methanol in polar and nonpolar solvents were studied by using the first overtone of O-H stretching vibrations observed in the near-infrared (NIR) band ranging from 7500 to 6000 cm −1 . To eliminate the absorption of solvents, NIR-inactive nonpolar solvents carbon tetrachloride (CCI4 ) and tetrachloroethylene (C2 CI4 ) were chosen, along with deuterium-substituted polar solvents acetone- d 6, acetonitrile- d 3, 1, 4-dioxane- d 8, and tetrahydrofuran (THF)- d 8 . The changes in the hydrogen-bonding states of methanol during mixing with the solvents were estimated using the extended molar absorption spectrum, which was defined as the concentration difference. The extended molar absorption spectra in different concentrations were decomposed into a finite number of independent factors using a multivariate curve resolution–alternating least squares calculation. Two and three such factors were sufficient to reproduce the extended molar absorption spectra for the nonpolar and polar solvents, respectively. The detailed assignments of each factor were estimated using the calculated loadings and scores. A similarity analysis was also applied to the extended molar absorption spectra of methanol and effectively quantified the deviation from the spectrum of pure methanol. The methanol and solvent affinities were also compared.